Cryptococcus infection in a non-HIV patient: a case report - Charmian D. Sittambalam; Heidi Hanna; Justin Martello; Dimitra Mitsani (Greater Baltimore Medical Center, 2012)
Cryptococcal infections are fungal infections most commonly seen in immunocompromised patients. Chronic high-dose steroid may precipitate such an immunocompromised state and thus create susceptibility to fungal infections. Cryptococcus neoformans is a saprophyte usually found in soil contaminated with pigeon droppings. Suspicion to diagnose begins with clinical symptoms that can be non-specific such as fevers, cough, and headaches. We present a case of steroid-induced cryptococcal infection in a non-HIV-infected person.